Railway station development in post-industrial Rotterdam - path dependency and shifting priorities - Jan Jacob Trip (European Regional Science Association (ERSA), 2005)
The combined effects of industrial decline and the development of a service economy currently bring about a change in urban economies. Accessibility, proximity and an attractive urban climate are considered important factors of urban competitiveness. These are all combined in railway station area, which is therefore considered a focus point of urban economic development. The paper investigates the role of station development projects in the perspective of these long-term social and institutional processes in contrast to the continuity found in a city's estab-lished economic structure, prevailing policy arenas, objectives and cultures. It does so by means of an analysis of station development in Rotterdam, a manufacturing and seaport city now strug-gling to find ways to develop a competitive service economy. The paper draws a comparison with Rotterdam's rival Amsterdam, showing that differences in present economic performance and urban development are partly rooted in different economic histories. The paper investigates to which extent these differences affect the role of major railway station redevelopment projects in both cities, and the way these projects are implemented.
Keywords: 330